1984
DOI: 10.1103/physrevb.30.93
|View full text |Cite
|
Sign up to set email alerts
|

Positron diffusion in germanium

Abstract: The temperature dependence of the diffusion constant of positrons in Ge single crystals is discussed. Experimental data on the fraction (fp, ) of 0 -5-keV incident positrons reemitted from the surface as positronium are presented for Ge over the temperature range 300& T & 1020 K. The positron diffusion constant is deduced, at various temperatures, from an analysis using a onedimensional diffusion model for fp, which is determined as a function of incident positron energy E. The magnitude and temperature depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…However, in the case of semiconductors with a narrow gap, this does not hinder thermalization appreciably; i.e. , the thermalization time is of the same order as in metals (Jorch et al , 1984). In the case of wide-band-gap insulators, electron-hole excitations are no longer possible when the positron energy reaches the region of a few eV's.…”
mentioning
confidence: 99%
“…However, in the case of semiconductors with a narrow gap, this does not hinder thermalization appreciably; i.e. , the thermalization time is of the same order as in metals (Jorch et al , 1984). In the case of wide-band-gap insulators, electron-hole excitations are no longer possible when the positron energy reaches the region of a few eV's.…”
mentioning
confidence: 99%
“…Figure 1 shows a plot of calculated results of Ps fraction (f ps) as a function of incident energy of positron for two temperatures in the case of Ge(110). The calculated results are compared with the experimental observations of Jorch et al [5]. One can see from these graphs that the general trends of the experimental curves are well reproduced.…”
Section: Resultsmentioning
confidence: 55%
“…Considering the exponential type of implantation profile and a = AEn, where E [keV] is the energy of the incident positrons. The value of n is taken to be 1.6 as per experimental observations [5]. The solution of Eq.…”
Section: Calculation Of Positronium Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), the positronium fraction Ps is constant at low temperatures up to 600 K and then it increases almost linearly with temperature up to 1100 K and after that it becomes nearly constant. These results have been compared with the available experimental results of Jorch and Lynn [13] in Table III. We have found that the calculated results agree well with the experimental ones.…”
Section: Resultsmentioning
confidence: 95%